2020
DOI: 10.3390/en13184685
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Free-Piston Hydrogen-Gasoline Engine Linear Generator

Abstract: The free-piston engine linear generator (FPELG) is being investigated by many researchers because of its high thermal efficiency and its variable compression ratio. However, all researchers focused on the FPELG characteristics with mono-fuel. Therefore, in this paper, the performance of the FPELG that has adopted gasoline with hydrogen as fuel is investigated. The method of coupling the zero-dimensional dynamics model with the multi-dimensional CFD (Computational Fluid Dynamics) combustion model was applied du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to recent research, thermal-electrical energy conversion can make considerable contributions to renewable energy globally. Thermal electrical energy converters with improved performance can compete with other types of fossil fuels and renewable energy sources in the energy market [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent research, thermal-electrical energy conversion can make considerable contributions to renewable energy globally. Thermal electrical energy converters with improved performance can compete with other types of fossil fuels and renewable energy sources in the energy market [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In FPEGs without a crank mechanism, the piston motion can be changed. As a result, the compression ratio (CR) can be changed to accommodate a variety of fuels, including hydrogen, which is a zero-carbon alternative fuel [8][9][10]. In addition, FPEGs have advantages such as reduced frictional loss because they have no crank mechanism [11,12] and improved thermal efficiency by varying the piston motion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that increasing the effective stroke of the cylinder increased the capture rate of fresh charge, but the scavenging efficiency decreased. Zuo et al 21,22 intend to effectively control the cylinder pressure of the free-piston internal combustion generator, a variable load control method is proposed to restrain the piston movement, and a closed-loop control strategy of variable load control is designed. The simulation results show that the variable load control based on the control strategy can make the piston movement tend to be stable, so as to realize the stable control of the cylinder pressure.…”
Section: Introductionmentioning
confidence: 99%